Intracranial Hemorrhage Following Oral Low-Dose Methotrexate After Multiple Toxicities Caused by High-Dose Methotrexate in Childhood Acute Lymphoblastic Leukemia - Xin, Ning; Fen, Zhou; Li, Cheng; Yan, Xiao; Runming, Jin (Frontiers in Pharmacology, 2019)
A 11-year-old male patient with IKZF1 deletion and BCR-ABL1-positive acute lymphoblastic leukemia appeared elevated levels of serum alanine aminotransferase and cholecystitis with the symptoms of vomiting, abdominal pain and diarrhea during the first course of high-dose methotrexate. He was admitted for myelosuppression, oral mucositis, rashes and dysfunction of liver during the second treatment of high-dose methotrexate. At last, intracranial hemorrhage occurred following oral methotrexate at doses of 25mg/m2, and CT scan of his brain showed increased intensities in multiple cerebral lobes. he had neurological sequelae of hemiplegic paralysis after six months.